Adventure guide. The Canadian Rockies / Brenda Koller - Koller, Brenda
We travel to grow - our Adventure Guides show you how. Experience the places you visit more directly, freshly, intensely than you would otherwise - sometimes best done on foot, in a canoe, or through cultural adventures like art courses, cooking classes, learning the language, meeting the people, joining in the festivals and celebrations. This can make your trip life-changing, unforgettable. All of the detailed information you need is here about the hotels, restaurants, shopping, sightseeing. But we also lead you to new discoveries, turning corners you haven''t turned before, helping you to i.